The "Crocodile Technique": A New Ophthalmic Surgical Technique to Remove Subretinal Proliferative Tissue Associated with Retinal Detachment - Tadayuki Nishide; Ikuko Kimura; Natsuki Hayakawa; Yoko Yagi; Etsuko Shibuya; Reiko Yasumura; Nobuhisa Mizuki (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2014)
Purpose: To describe the "crocodile technique", a new ophthalmic surgery technique for removing subretinal proliferative tissue (SPT) associated with retinal detachment. Materials and Methods: Subjects were 21 patients who had retinal detachment with SPT. Their follow-up terms were all greater than 3 months. We undertook the crocodile technique during their subretinal surgery. The crocodile technique is a new ophthalmic technique for removing SPT using vitreous forceps, without using subretinal forceps, in small-gauge vitrectomy. After performing sufficient peripheral vitrectomy, a small intentional retinal tear was created above the SPT. The SPT was then stabilized while grasped by vitreous forceps in the subretinal space. The vitreous forceps were then rotated on their long axis, such that the SPT was rolled around the vitreous forceps in the subretinal space. Results: The crocodile technique was successfully performed without enlarging the intentional retinal tear or creating new retinal tears, in all subjects. The retina was successfully reattached in all subjects, postoperative average visual acuity was improved after surgery, and postoperative redetachment did not occur in any patients. Conclusions: The crocodile technique can be performed without subretinal forceps. Using the technique, retinal detachment with SPT can be treated using vitreous forceps in small-gaugevitrectomy.